Perilaku Prokrastinasi: Berbasis Performansi Kerja - Nugraha J, Albert Adityas; Hadi, Cholichul (Universitas Airlangga, 2022)
Procrastination is an intense behavior tendency to delay a task or a job for both short or long periods, which can create bad situations. Bad situations mentioned in this research are neither for the employee itself and for the organization widely. Procrastination could decrease employee's performance, organization effectiveness, and also could create stress conditions for others. The purpose of this research is to see the relation between an employee's procrastination behavior with their performance in organization. This research used Irrational Procrastination Scale (IPS) to measure the procrastination behavior tendency. Participant of this research is focused on employee that currently active in an organization, and has minimum a year of service.